SOME NOTES ON TAYRA Eira barbara (Linnaeus, 1758) (MUSTELIDAE: GULONINAE) IN PARAGUAY - Ortega, Carlos; Segovia, Pamela; Smith, Paul (Revista Nordestina de Zoologia, 2025)
The Tayra Eira barbara (Mustelidae: Guloninae) is a widespread mesocarnivore that has been documented from all Paraguayan departments except Amambay, Cordillera and Misiones. We provide photographic documentation of the species in the former department at Parque Nacional Cerro Corá, further increasing the presence of the species within the Paraguayan protected area system. We provide two further observations of note, a possibly xanthochromistic individual in captivity in Paraguay and an observation of a breeding den. Though declining, the species is considered to face no conservation threats in Paraguay.